The use of mineral materials for salinity control in roadside soils - Katarzyna Łuczak; Izabella Pisarek; Grzegorz Kusza (Archives of Environmental Protection, 2020)
This paper presents the results of a fi eld study on using mineral materials (fine-grained sand and medium-grained gravel) to reduce the concentration of readily soluble salts in a roadside environment. The investigated soils were Rendzic Sceletic Leptosols from an urban area characterized by a shallow humus horizon with a high content of skeletal parts, as well as a lack of homogeneity of the material in the soil profile. All soil samples were taken from five plots located along the main streets in the city of Opole (Southern Poland). It was revealed that the use of fine-grained sand and medium-grained gravel improved the structure of the surface soil layer, and thus favoured the migration of Na+ and Cl- ions into the soil profile. In comparison to control surfaces readily soluble salts were reduced with gravel and sand application. Furthermore, the mineral materials introduced on the soil surface for salinity neutralization did not affect the quality of the tested roadside calcareous soils. The results indicate that the use of mineral materials reduces soil salinity caused by NaCl. They also show the need to find new methods of salt neutralization, especially of roadside soils in order to improve and protect the quality of the environment.